Delayed eruption of permanent maxillary first molars among Saudi children: A cross-sectional study - Omar A. Bawazir; Noor W. Abahussain; Tuga A. Alduwayan; Ayman M. Sulimany (Saudi Dental Journal)
Aim: This retrospective cross-sectional study aimed to determine the prevalence of delayed development and eruption of permanent maxillary first molars (U6) and associated dental anomalies in a sample of Saudi children. Material and methods: In total, 10,232 panoramic radiographs from 9,672 patients were screened for delayed U6 eruption. Radiographs showing delayed U6 eruption were further examined for associated dental anomalies. The dental age of participants was estimated using The London Atlas of Human Tooth Development and Eruption. Result: Twenty cases of delayed U6 eruption were found, with a prevalence of 0.2%. Of these patients, 3 and 17 were males and females, respectively; 9 and 11 cases were unilateral and bilateral, respectively. Congenital absence of the adjacent permanent second molar was observed in 8 cases, and the congenital absence of permanent teeth, except the adjacent second permanent molar and third molar, was observed in 6 cases. Peg-shaped lateral incisors were observed in 6 females. No significant associations were observed between delayed U6 eruption and dental anomalies. Overall, the average delayed U6 eruption was 2.3 years for males and 2.8 years for females. Conclusion: Among a sample of Saudi children, the prevalence of delayed U6 eruption was 1 in 483 (0.2%) and five times higher in females. No significant associations were found between delayed U6 eruption and dental anomalies; however, congenital absence of the adjacent permanent second molar was observed in 40% of cases.